Third Five-Year Plan of Andhra Pradesh Annual Plan for 1962-63 - Planning Commission (Planning Commission, 1962)
Summary Statement of State Plan outlay for 1962-63 List of schemes included in the State Plan for 1962-63 List of schemes included in the State Plan for 1962-63 List of Centrally Sponsored Schemes to be implemented in 1962-63.
Planning and Local Administration Department, Hyderabad